Effect of different intensity exercises intervention on cardiovascular functions and quality of life on patients with chronic heart failure: A protocol for systematic review and meta-analysis. Issue 2 (14th January 2022) - Bai, Yan; Hua, Bin; Zhang, Fan; Zhou, Wenqin; Deng, Bing
Abstract: Background: Exercise training can improve exercise capacity, quality of life, and reduce hospitalization time in chronic heart failure (CHF) patients. Various training protocols have been studied in CHF, but there is no consensus on the optimal exercise intensity for the rehabilitation of cardiac patients. Therefore, systematic evaluation of the effects of different exercise intensities on the efficacy of cardiac function and quality of life in patients with CHF was done. Methods: Computer searches of PubMed, Web of Science, The Cochrane Library, Embase, SinoMed, the China National Knowledge Infrastructure, Wanfang, and VIP databases were conducted to collect randomized controlled trials of different exercise intensities applied to patients with CHF. Study selection and data extraction will be performed simultaneously by two independent reviewers, using the PEDro scale for quality assessment of the included literature. Publication bias will be assessed by funnel plot, and Begg and Egger tests. The I 2 statistic and the chi-square ( χ 2 ) test will be used to assess heterogeneity. In addition, subgroup analyses will be performed for different left ventricular ejection fraction populations and different intervention cycles. All meta-analyses will be performed using Revman5.3 software. Results: The present study is a systematic review and meta-analysis program with no results. Data analysis will be completed after the program has been completed. Conclusion: This meta-analysis may provide more reliable, evidence-based evidence for the choice of exercise intensity in patients with CHF. Registration number: CRD42021276529